Computer-assisted surgery: Virtual- and augmented-reality displays for navigation during urological interventions - Van Oosterom, Matthias N.; Van Der Poel, Henk G.; Navab, Nassir; Van De Vede, Cornelis J. H.; Van Leeuwen, Fijs W. B. (Current Opinion in Urology, 2018)
Purpose of review To provide an overview of the developments made for virtual- and augmented-reality navigation procedures in urological interventions/surgery. Recent findings Navigation efforts have demonstrated potential in the field of urology by supporting guidance for various disorders. The navigation approaches differ between the individual indications, but seem interchangeable to a certain extent. An increasing number of pre- and intra-operative imaging modalities has been used to create detailed surgical roadmaps, namely: (cone-beam) computed tomography, MRI, ultrasound, and single-photon emission computed tomography. Registration of these surgical roadmaps with the real-life surgical view has occurred in different forms (e.g. electromagnetic, mechanical, vision, or near-infrared optical-based), whereby the combination of approaches was suggested to provide superior outcome. Soft-tissue deformations demand the use of confirmatory interventional (imaging) modalities. This has resulted in the introduction of new intraoperative modalities such as drop-in US, transurethral US, (drop-in) gamma probes and fluorescence cameras. These noninvasive modalities provide an alternative to invasive technologies that expose the patients to X-ray doses. Whereas some reports have indicated navigation setups provide equal or better results than conventional approaches, most trials have been performed in relatively small patient groups and clear follow-up data are missing. Summary The reported computer-assisted surgery research concepts provide a glimpse in to the future application of navigation technologies in the field of urology.
CRIS-Team Scopus Importer:2023-03-08
Keywords: augmented reality; image-guided surgery; surgical navigation; urology; virtual reality